(untitled) (E Conference Zone, 2022)
The education system is the main social structure of each state that needs special attention, and every government that comes to power seeks to improve this system in its domestic policy. The creation of a production system based on new modern technologies based on scientific achievements, which will serve to increase the economic potential of the country, is directly related to education. If we look closely, we can see that serious attention to education is under the personal control of state leaders. This shows that the education system is an important area of social life. In particular, we can see that in the second half of the 19th century and the beginning of the 20th century, the governments that came to power in Great Britain also tried to implement reforms to improve the education system and its condition. We will try to analyze as much as possible the contradictions, debates, discussions and results of the implementation of these reforms